Structures and Their Analysis - Fuchs, Maurice Bernard (Springer International Publishing : Imprint: Springer, 2016)
Addressing structures, this book presents a classic discipline in a modern setting by combining illustrated examples with insights into the solutions. It is the fruit of the author's many years of teaching the subject and of just as many years of research into the design of optimal structures. Although intended for an advanced level of instruction it has an undergraduate course at its core. Further, the book was written with the advantage of having massive computer power in the background, an aspect which changes the entire approach to many engineering disciplines and in particular to structures. This paradigm shift has dislodged the force (flexibility) method from its former prominence and paved the way for the displacement (stiffness) method, despite the multitude of linear equations it spawns. In this book, however, both methods are taught: the force method offers a perfect vehicle for understanding structural behavior, bearing in mind that it is the displacement method which does the heavy number crunching. As a rule the book keeps things as simple as possible, conveying the basic ideas and refraining from lengthy calculations wherever possible. Further, it endeavors to unify the approach, showing that whatever applies to simple springs is equally valid for intricate frames. In addition to various design considerations, it also addresses several topics relating to optimal structures that will be of interest to students and teachers of structures.